Direct and simultaneous spectrophotometric determination of Ni (II) and Co (II) using diethanoldithiocarbamate as complexing agent - Antunes,P. A. (2009)
A direct spectrophotometric method for simultaneous determination of Co(II) and Ni(II), with diethanoldithiocarbamate (DEDC) as complexing agent, is proposed using the maximum absorption at 360 and 638 nm (Co(II)/DEDC) and 390 nm (Ni/DEDC). Adjusting the best metal/ligand ratio, supporting eletrolite, pH, and time of analysis, linear analytical curves from 1.0 10-6-4.0 10-4 for Co(II) in the presence of Ni 1.0 10-6-1.0 10-4 mol L-1 were observed. No further treatment or calculation processes have been necessary. Recoveries in different mixing ratios were of 99%. Interference of Fe(III), Cu(II), Zn(II) and Cd(II), and anions as NO3-, Cl-, ClO4-, citrate and phosphate has been evaluated. The method was applied to natural waters spiked with the cations.